Identifikasi Kandungan Formalin Pada Tahu Putih Di Pasar Tradisional Kecamatan Klaten Tengah dengan Metode Spektrofotometri UV-Vis - Alifia Nuraini; Meila Diana; Arifah, Mitsalina Fildzah (CERATA Jurnal Ilmu Farmasi, 2025)
White tofu is a high-protein food widely consumed by the public but has a short shelf life due to its high water content. To extend its shelf life, some vendors use formalin as a preservative, although its use is prohibited due to its toxic nature and potential to cause digestive disorders, organ damage, and cancer. Traditional markets in Central Klaten District serve as economic centers for the local community; however, information regarding the presence of formalin in white tofu remains limited. This study aimed to identify presence of formalin in white tofu sold at these markets, qualitatively and quantitatively. A non-experimental descriptive design was used, involving organoleptic testing over three days, qualitative analysis using KMnO4, Fehling A & B, Schiff, and chromotropic acid reagents, determination of the maximum wavelength, and quantitative analysis using the UV-Vis spectrophotometry method. Signs of spoilage were observed in all samples through organoleptic testing. No colour change was detected in qualitative analysis, and no absorption peak was observed at 580 nm. The validity of the UV-Vis spectrophotometry method was demonstrated by a linearity and linear range with r = 0.999, %Recovery from accuracy of 97.807-101.023%, %RSD from precision were 1.206%, a limit of detection (LOD) of 2.811 ppm, and a limit of quantification (LOQ) of 8.519 ppm. Samples suspected of containing formalin were confirmed to be free of formalin based on the quantitative test. The limitation of this study was its lack of sensitivity toward very low formalin concentrations. In conclusion, formalin was not detected in any sample through organoleptic, qualitative, and quantitative test. The validity of the UV-Vis spectrophotometry method met the required validation parameters.